New Muslim women of Bangladesh - Hussein, Nazia, author.
1 online resource.
Keywords: "This book reveals how categories of gender, class, culture and religion are modes of power which inform hierarchies of social locations and people's sense of belonging within these spaces and temporalities. It offers an alternative and innovative theoretical framework - new womanhood - for studying middle-class, urban, educated, professional women in South Asia. The book places respectable femininity at the centre of the construction and performance of new womanhood in Bangladesh: a complex and heterogeneous construction of womanhood in relation to women's negotiations with public and private sphere roles and cultural norms of female propriety. It establishes new women as part of the neoliberal middle class as they construct their class identity as a status group, claiming inter-class and intra-class distinction from other women. It also explains how new womanhood is legitimized by alternative and multiple practices of respectability, varying according to women's age, stage of life, profession, household setting and experience of living in western countries. Finally, as new women forge alternative forms of respectability theirs is not a straightforward abandonment of old structures of respectability; rather they, substitute, conceal, or legitimize particular practices of respectability in particular fields. While these new women's gains are vested in the self, rather than a wider feminist politics, they have the potential to positively influence the terrain of possibilities for other women. Finally, through a study of cosmopolitan third world women who are part of a new and potentially powerful social group who occupy a privileged position in the society they live in, the book critiques Western feminist writing and challenges binary social construction of the 'Muslim woman' either as victims of patriarchal culture and religion or as a danger to Western liberalism, developing an understanding of cosmopolitan Muslim women's classed gender identity as a struggle against classifications in the neo-liberal times. It is the first book length project of its kind to provide an understanding of the concept of new women in the Global South, which will be of interest to academics in the fields of sociology, gender studies, feminist theory, postcolonialism, inequality studies, cultural theory, development studies and South Asian Studies"--